Efektivitas Immunoterapi Dalam Tatalaksana Guillain-Barré Syndrome Pada Anak - Giovanni Reynaldo; Audrey Desiree (Jurnal Kedokteran Meditek, 2019)
Guillain-Barré Syndrome (GBS) is an immune-mediated inflammatory disorder of the peripheral nervous system in which an autoimmune response is directed against peripheral nerves. The pathogenesis of GBS is believed to be an abnormal immune response to an antecedent event, most commonly an infection, and in a few cases associated with vaccination especially in children. The clinical manifestation of GBS is rapid and ascending progressive bilateral limb weakness. Therapies which are still being used and considered effective are intravenous immunoglobulin and plasmapheresis. New modalities such as Interferon-β (IFN-β), Cyclophosphamide, and Human Monoclonal Antibody still require further study related to the effectiveness and potential side effects. The prognosis of GBS in children is much better, the mortality rate is also very low, affecting 1-2% of children with GBS, while only 4% of paediatric patients are in need of respiratory support during hospitalisation.